Description of the movement of the Endangered Chaco Tortoise Chelonoidis chilensis - Kazimierski, Laila Daniela (2025)
The Chaco Tortoise Chelonoidis chilensis is the southernmost species of land tortoisein the world. This species is currently listed as Endangered not only due to habitat reduction anddestruction, but also because of its value in the illegal pet trade. As both a grazer and a seeddisperser, it serves as a keystone species in the dry ecosystems it inhabits. Despite its endangeredstatus and important ecological role, there is currently limited information on the movement patterns of C. chilensis. In this work, we investigated the movement characteristics of this species over two seasons and in both sexes, using three complementary tracking techniques of spool-and-line, radiotelemetry, and GPS-based tracking, including the use of a device designed and developed by our team. To capture the most comprehensive view of movement patterns, each of the techniques used provides distinct strengths in characterizing spatial or temporal aspects of movement. We studied the movements of the tortoises over two seasons (spring 2020 and summer 2021), in their natural habitat near the city of San Antonio Oeste, Río Negro, Argentina. We tracked seven individuals (four males and three females) with the spool-and-line technique, 12 (six males and six females) with radiotelemetry, and 10 (four males and six females) with the GPS-based system. We estimated their daily home range (DHR) and speed of movement, measured the tortuosity of the walks and characterized their mean square displacement. The results indicated that C. chilensis remains within a DHR of 864 ± 283 m² in the spring season and 1034 ± 298 m² in the summer season. The most probable value of their velocity is 0.4 ± 0.1 m/min, with a median value of 0.6 ± 0.1 m/min, and the walks are characterized by bouts of foraging during movement, with periods of time spent exploring new spaces while also maintaining activity within their home ranges. Notably, we observed that C. chilensis can travel as much as 400 m in one day. The complementarity of our monitoring techniques allowed us to study and characterize the movement of this species at different scales. For example, the high spatial resolution of the spool-and-line technique can describe tortuosity, while the GPS-based and radiotelemetry techniques can describe trajectories with fine temporal resolution. To better understand how these animals move, the distances they can travel daily, and how these results depend on the season are relevant for making conservation decisions, while considering the significant impact that habitat fragmentation and other factors can have on their environment.